Pengaruh Work Life Balance dan Job Satisfaction terhadap Turnover Intention Karyawan RS X - Sri Hartini; Hulu, Niceh Christiani; Widyaningtyas Caturini Pratisya; Bianca Herlianti Kusuma; Elvinawanty, Rianda; Ndruru, Bernad Ekarisman (Jurnal Ragam Pengabdian, 2026)
This study examines the effect of work-life balance and job satisfaction on turnover intention among employees of Hospital X. The background of this research is based on the increasing phenomenon of employee turnover intention in healthcare organizations, which may disrupt service continuity and organizational performance. The objective of this study is to analyze the partial and simultaneous effects of work-life balance and job satisfaction on turnover intention. This research employed a quantitative approach with a cross-sectional design. The population consisted of 75 employees from both medical and non-medical units, using total sampling technique. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 25. The results show that work-life balance and job satisfaction simultaneously have a significant effect on turnover intention (F = 70.525; p < 0.05), with an Adjusted R Square of 0.653, indicating that 65.3% of turnover intention variance is explained by the model. Partially, both work-life balance and job satisfaction significantly influence turnover intention, with job satisfaction as the most dominant variable. In conclusion, turnover intention is influenced by both psychological and work-related factors in an integrated manner. It is recommended that hospital management improve employee job satisfaction and maintain work-life balance to reduce turnover intention. The implication of this study is that human resource management strategies in healthcare institutions should focus on improving working conditions and employee well-being to enhance retention and organizational stability.